2010
DOI: 10.1038/npp.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Mediates the Interface between Motivational and Cognitive Control in Humans: Evidence from Genetic Imaging

Abstract: Dopamine has been hypothesized to provide the basis for the interaction between motivational and cognitive control. However, there is no evidence for this hypothesis in humans. We fill this gap by using fMRI, a novel behavioral paradigm and a common polymorphism in the DAT1 gene (SLC6A3). Carriers of the 9-repeat (9R) allele of a 40 base pair repeat polymorphism in the 3 0 untranslated region of DAT1, associated with high striatal dopamine, showed greater activity in the ventromedial striatum during reward ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
132
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 48 publications
21
132
5
Order By: Relevance
“…No behavioral or neural interactions between motivation and cognitive control were found, leading to the conclusion that motivation and cognitive control are two independent systems operating in parallel during decision making. However, these findings are incongruent with recent behavioral and neuroimaging studies suggesting that motivation has differential effects depending on the type or level of cognitive control (Dreisbach and Goschke, 2004;Rowe et al, 2007; for reviews, see Pessoa, 2009;Aarts et al, 2011). Nevertheless, these studies did not use different levels of cognitive control to engage the rostro-caudal gradient in the lateral frontal cortex.…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…No behavioral or neural interactions between motivation and cognitive control were found, leading to the conclusion that motivation and cognitive control are two independent systems operating in parallel during decision making. However, these findings are incongruent with recent behavioral and neuroimaging studies suggesting that motivation has differential effects depending on the type or level of cognitive control (Dreisbach and Goschke, 2004;Rowe et al, 2007; for reviews, see Pessoa, 2009;Aarts et al, 2011). Nevertheless, these studies did not use different levels of cognitive control to engage the rostro-caudal gradient in the lateral frontal cortex.…”
Section: Introductioncontrasting
confidence: 55%
“…First, motivation and cognitive control are modular and operate as two independent systems represented in distinct medial (motivation) and lateral (levels of cognitive control) frontal regions (Kouneiher et al, 2009;Charron and Koechlin, 2010). Alternatively, these systems interact (Dreisbach and Goschke, 2004;Pessoa and Engelmann, 2010;Aarts et al, 2011) such that motivation modifies levels of cognitive control differentially to shape human behavior and these motivation-cognition interactions can take place in both medial and lateral frontal regions. Given evidence suggesting that dopamine is critical for motivation (Berridge and Robinson, 1998) and cognitive control (Cools and D'Esposito, 2011), we also tested the hypothesis that functional connectivity between dopamine-rich midbrain regions and frontal cortex would differ as a function of motivation and levels of cognitive control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent genetic imaging studies have shown that task set switching also varies as a function of individual genetic differences in DA function, particularly when subjects are expecting to be rewarded (Aarts et al, 2010). The latter study revealed that this DA-dependent effect of reward on task set switching was accompanied by modulation of the dorsomedial part of the striatum (Aarts et al, 2010), further highlighting that effects of DA on task set switching might occur via modulation of different dopaminergic target regions in more dorsal parts of the striatum than those associated with reversal learning, which rather implicates the ventral striatum (Cools et al, 2001).…”
Section: Perseveration and Switchingmentioning
confidence: 99%